6(5x+1)=2x-8x

Simple and best practice solution for 6(5x+1)=2x-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(5x+1)=2x-8x equation:


Simplifying
6(5x + 1) = 2x + -8x

Reorder the terms:
6(1 + 5x) = 2x + -8x
(1 * 6 + 5x * 6) = 2x + -8x
(6 + 30x) = 2x + -8x

Combine like terms: 2x + -8x = -6x
6 + 30x = -6x

Solving
6 + 30x = -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
6 + 30x + 6x = -6x + 6x

Combine like terms: 30x + 6x = 36x
6 + 36x = -6x + 6x

Combine like terms: -6x + 6x = 0
6 + 36x = 0

Add '-6' to each side of the equation.
6 + -6 + 36x = 0 + -6

Combine like terms: 6 + -6 = 0
0 + 36x = 0 + -6
36x = 0 + -6

Combine like terms: 0 + -6 = -6
36x = -6

Divide each side by '36'.
x = -0.1666666667

Simplifying
x = -0.1666666667

See similar equations:

| 378=18xz | | 71-6x=12x+15 | | 3(-2a+2)=9a-10 | | 13-10x=37-24x | | 3(-2+2)=9a-10 | | 2x+3x-12=4x-25 | | -127-8x=7x+23 | | 10+p=23 | | 3=10v-(-4v+1) | | k-13=18 | | 4x+6=-49-7x | | 3=10v-(4v+1) | | 75-3x=2x+15 | | 9+x=16 | | -1=-(3-8k)-k | | -8=-7m-(-3m+2) | | 6a-3(6-4a)=-6 | | 5x+78=11x+12 | | 65t=390 | | y-8=605 | | c-4=5 | | 18=b+9 | | 3(8n+2)+2=2-9n | | 5m-(-45k)+10m-10k= | | x+68=110 | | 3x^2-2=5x | | -5(-9a+3)=-4(-5-8a) | | n-5(n-3)=-n+6 | | -7-3x=3(3x+6) | | 12c^2+11c-15=0 | | 6x^2+13x-35=0 | | 12x^2+13x-35=0 |

Equations solver categories